Analisis Penurunan Ballast Akibat Beban Tahunan Kereta Api (Passing Tonnage) Pada Segmen Jember - Kalisat: Analysis Of Ballast Settlement Due To Annual Train Loads (Passing Tonnage) On The Jember - Kalisat Segment - Pradana, Putri Amabel Carissa; Purnamasari, Fitriana; Alfiansyah, Achmad Dzulfiqar (Media Ilmiah Teknik Sipil, 2025)
Most of the railway lines in Indonesia use a ballasted track system, including the Jember–Kalisat line in Operational Area IX Jember which is the location of this research. The rail structure consists of a superstructure (rails, tethers, sleepers) and a substructure (ballast layer, sub-ballast, subgrade), which must meet technical specifications according to PM 60 of 2012. The ballast layer is the initial layer that receives load distribution from the upper structure, so it requires routine maintenance to maintain stability. This research aims to estimate the decline in the ballast layer due to annual loads using a quantitative approach. The calculation results show that the annual tonnage on the Jember–Kalisat segment is 17,328,960 tons/year, which is in accordance with class II route specifications. Field measurements at five sample points showed that the ballast thickness did not meet the standard, namely 30 cm, so it was estimated that there would be a greater decrease compared to standard conditions. The largest estimated decrease occurred at KM 202+200 to KM 202+300, with a decrease of 4.06 cm per year upstream and 3.36 cm per year downstream. This calculation also produces an estimated graph of ballast layer reduction based on annual tonnage. It is hoped that this research can provide important recommendations regarding ballast layer maintenance to maintain railway track stability.